Transposition of a national sports event into a transnational one on the example of the Spanish El Clásico - Górnicka, Weronika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented article focuses on the analysis of the transposition of a national event into supranational one, the most striking example of which is the confrontation of Real Madrid with FC Barcelona, known as El Clásico. The text will examine the elements used in the process of recasting the event, which are decisive for giving it a meaning beyond the framework of a single country.
Keywords: El Clásico; national sport events; sport; reification; social identity